Evaluasi Kinerja Simpang Tak Bersinyal Dengan Pulau Lalu Lintas di Kota Pontianak: Studi Kasus : Persimpangan Jl. Tebu-Jl. Tabrani Ahmad - Muhammad Dzulfikar Andika Satriatama; Elsa Tri Mukti; S. Nurlaily Kadarini (JURAL RISET RUMPUN ILMU TEKNIK, 2025)
The increase in traffic volume in urban areas often triggers various problems, especially at Road intersection points that have a high level of interaction between vehicles. One of the locations that experience these problems is the intersection with the island of traffic without signal on Jl. Tebu-Jl. Tabrani Ahmad, City Of Pontianak. This study aims to analyze the performance of the intersection in the existing condition and project its performance in the next five years (2030), as well as formulate alternative treatment that can improve the smoothness of traffic. The analysis method refers to Indonesian road capacity guidelines (PKJI) 2023 and modeling using software PTV VISSIM. The data collected include intersection geometry, traffic volume, and vehicle speed. Traffic volumes were obtained through CCTV recordings for three consecutive days, then processed and presented in the form of tables and graphs for easy interpretation. The results of the existing condition analysis showed that the degree of saturation (DS) reached 0.407 with an average delay of 9.539 seconds (Level of Service/LOS B) based on PKJI, while VISSIM simulation resulted in a delay of 12.54 seconds (LOS B). The five-year projection (2030) shows an increase in DS to 0.878 with a delay of 15.177 seconds (LOS C) from PKJI, and 23.35 seconds (LOS C) from VISSIM, which indicates a decrease in Junction performance as traffic grows. Two handling alternatives were analyzed, namely the construction of roundabouts and the implementation of traffic flow management. VISSIM simulation shows that the roundabout can reduce the delay to 14.31 seconds with a queue length of 20.34 m (LOS B), while the flow management produces a delay of 11.81 seconds with a queue of 13.14 m (LOS B). This result confirms that both alternatives are able to improve the performance of the intersection compared to the projected condition without handling, so that it can be a technical recommendation for urban traffic planning in Pontianak.